2011
DOI: 10.1101/lm.1895211
|View full text |Cite
|
Sign up to set email alerts
|

Ventral tegmental area and substantia nigra neural correlates of spatial learning

Abstract: The ventral tegmental area (VTA) and substantia nigra pars compacta (SNc) may provide modulatory signals that, respectively, influence hippocampal (HPC)-and striatal-dependent memory. Electrophysiological studies investigating neural correlates of learning and memory of dopamine (DA) neurons during classical conditioning tasks have found DA neural activity in VTA and SNc to be tightly coupled with reinforcement expectations. Also, VTA integrity and DA in HPC have been found to regulate the encoding of HPC-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 75 publications
(93 reference statements)
1
17
0
Order By: Relevance
“…Additionally, the hippocampus and VTA appear to form a functional loop wherein information is not just sent downstream from the hippocampus to the VTA, but that subsequent processing of contextual information by the VTA is then sent back to the hippocampus for updating. Indeed, inactivation of the VTA has been shown to disrupt the stability of hippocampal place fields and increase in behavioral errors on a hippocampal-dependent working memory task (Martig and Mizumori, 2011). Another pathway linking the hippocampus and the VTA is the CA3-lateral septum-VTA pathway.…”
Section: Functional Pathways From the Hippocampus To The Vtamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the hippocampus and VTA appear to form a functional loop wherein information is not just sent downstream from the hippocampus to the VTA, but that subsequent processing of contextual information by the VTA is then sent back to the hippocampus for updating. Indeed, inactivation of the VTA has been shown to disrupt the stability of hippocampal place fields and increase in behavioral errors on a hippocampal-dependent working memory task (Martig and Mizumori, 2011). Another pathway linking the hippocampus and the VTA is the CA3-lateral septum-VTA pathway.…”
Section: Functional Pathways From the Hippocampus To The Vtamentioning
confidence: 99%
“…Since both decision and memory systems include cortical processing (and presumably, expectancy for action outcomes), we tested rats as they freely navigated a goal-directed spatial task that allows one to assess not only the relationship between neural responses and behavioral choices but also between neural responses and behaviors that lead to and follow a choice. All of the decision and memory brain structures recorded show strong neural firing that correlated with rats' velocity or acceleration of forward movement including prefrontal cortex, orbital frontal cortex, parietal cortex, retrosplenial cortex, entorhinal cortex, hippocampus, amygdala, striatum, and many midbrain regions such as the VTA, substantia nigra (SN), pedunculopontine tegmentum (PPTg), and the lateral dorsal tegmentum (LDTg; Eshenko and Mizumori, 2007;Jo et al, 2013;Martig and Mizumori, 2011;McNaughton et al, 1983McNaughton et al, , 1994Norton et al, 2011;Mizumori, 1998, 2001;Puryear et al, 2010;Redila et al, 2015;Smith et al, 2011). Neurons in only a subset of these brain structures also fire phasically to specific behavioral acts such as turning right or turning left on a maze (parietal cortex, striatum, and LDTg).…”
Section: Egocentric Movement Information Is Represented By Most Brainmentioning
confidence: 99%
“…The majority of dopaminergic innervations to the hippocampus (HPC) arise from the ventral tegmental area (VTA) as mesolimbic system, it was demonstrated that dopaminergic afferents from the VTA can stimulate neurogenesis and facilitate long-term synaptic plasticity in the HPC (Bethus et al 2010;Martig et al . 2011;Ghanbarian et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The non-motor symptoms that include cognitive deficits can be more important than the motor deficits to determine the patients' quality of life and represent an important factor to determine the need for nursing home care (Martig et al 2011;Hanna-Pladdy et al 2013). However, studies conducted over the last two decades have shown that cognitive impairments, including spatial working memory deficits, occur even in the early stage of PD when motor symptoms are barely observed (Hirano et al 2003;Varcin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, preclinical studies have indicate that VTA egocentric coding was strongest during initial training and coincided with the time that the rats learned the win-shift spatial working memory task (Martig and Mizumori 2011), and inactivation of the VTA selectively disrupted shortterm components of this working memory (Martig et al 2009). Additionally, intra-VTA injections of an NMDA antagonist immediately after training impaired the consolidation and persistence of fear long-term memory in rats (Mahmoodi et al 2010;Rossato et al 2009).…”
Section: Discussionmentioning
confidence: 97%